2020
DOI: 10.1007/s00705-020-04683-7
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus surveillance of wildlife in the Lao People’s Democratic Republic detects viral RNA in rodents

Abstract: Coronaviruses can become zoonotic, as in the case of COVID-19, and hunting, sale, and consumption of wild animals in Southeast Asia increases the risk for such incidents. We sampled and tested rodents (851) and other mammals and found betacoronavirus RNA in 12 rodents. The sequences belong to two separate genetic clusters and are closely related to those of known rodent coronaviruses detected in the region and distantly related to those of human coronaviruses OC43 and HKU1. Considering the close human-wildlife… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“… 12 , 157 , 180 184 A recent study suggests increasing coronavirus prevalence associated with the wildlife trade with increased disease along the trade route. 185 Palm Civets and Racoon Dogs previously detected with SARS-CoV infection exhibited symptoms and signs of distress. Similarly, this was observed for smuggled Sunda Pangolins in China that were positive for the closely related Pangolin-CoV.…”
Section: Wild-caught Positive Animalsmentioning
confidence: 99%
“… 12 , 157 , 180 184 A recent study suggests increasing coronavirus prevalence associated with the wildlife trade with increased disease along the trade route. 185 Palm Civets and Racoon Dogs previously detected with SARS-CoV infection exhibited symptoms and signs of distress. Similarly, this was observed for smuggled Sunda Pangolins in China that were positive for the closely related Pangolin-CoV.…”
Section: Wild-caught Positive Animalsmentioning
confidence: 99%
“…Identification of an OC43 subgroup virus in deer mice provides further evidence of the wide host range of this group of betacoronaviruses. A recent survey of Laotian wildlife found rodent coronaviruses in two distinct genetic clusters, one of which is related to OC43 [34]. Monchatre-Leroy et al found one rodent and five rabbit coronaviruses in France that belong to this group [35].…”
Section: Discussionmentioning
confidence: 99%
“…Two conventional nested broad range PCR assays, designed based on different sequence sets, both targeting different conserved regions within the RNA-dependent RNA polymerase gene (RdRp) were used successfully to screen samples of bats, rodents, and other animals (and humans) for CoV RNA ( Anthony et al. 2017 ; McIver et al. 2020 ; Kumakamba et al.…”
Section: Methodsmentioning
confidence: 99%